Van Gogh's Van Goghs masterpieces from the Van Gogh Museum, Amsterdam - Kendall, Richard; Gogh, Vincent van 1853-1890.; Leighton, John.; Heugten, Sjraar van.; Van Gogh Museum, Amsterdam; National Gallery of Art (U.S.).; Los Angeles County Museum of Art. (Washington National Gallery of Art New York Distributed by H.N. Abrams, 1998)
"Van Gogh's Van Goghs presents seventy paintings from the extraordinary collection of the Van Gogh Museum, Amsterdam, home to the single greatest assemblage of the artist's paintings, drawings, and letters. The collection is based on works acquired directly from the artist by his brother Theo, an art dealer and the source of Vincent's financial and emotional support. All periods of Vincent van Gogh's brief but intensely productive career are represented: his earliest paintings in The Netherlands; his responses to French Impressionism in 1886; the images he painted while in hospitals in Arles and Saint-Remy in southern France; and his last, feverishly creative works in Auvers-sur-Oise. Van Gogh's Van Goghs represents a unique opportunity to sample the largest and most varied Van Gogh collection in the world. It accompanies a major exhibition organized by the National Gallery of Art, Washington, and the Van Gogh Museum, Amsterdam, in collaboration with the Los Angeles County Museum of Art."--BOOK JACKET.
The Van Gogh Museum : a history of the collection / John Leighton -- Evangelism by other means : Van Gogh as a painter / Richard Kendall -- The life of Vincent van Gogh / Sjraar van Heugten.
Catalog of an exhibition to be held at the National Gallery of Art, Oct. 4, 1998-Jan 3, 1999 and at the Los Angeles County Museum of Art, Jan. 17-Apr. 4, 1999.
Includes bibliographical references (pages 158) and index.
Keywords: Gogh, Vincent van -- 1853-1890 -- Exhibitions; Van Gogh Museum, Amsterdam -- Exhibitions; Painting -- Netherlands -- Amsterdam -- Exhibitions